﻿A new cryptic species of land snail from the Northern Territory, Australia (Stylommatophora, Camaenidae, Parglogenia) - Frank Köhler; Michael Shea (Zoosystematics and Evolution, 2022)
Parglogenia cobourgensis sp. nov., a new species of camaenid land snail is described from Cobourg Peninsula, Top End of the Northern Territory in Australia. This new species has a shell that is identical to the type species of the genus, Parglogenia pelodes, which also occurs in the Top End. However, both species clearly differ in their reproductive anatomy and are also well-differentiated in terms of mitochondrial phylogenetics. A single specimen of a Parglogenia species from Croker Island, West Arnhem Land, is hypothesized to represent a third species based on details of its reproductive anatomy. However, only a single historical specimen was available for study. We therefore refrain from formally naming this species because of the incomplete information at hand. Helix subgranosa Le Guillou, 1842, a nominal species previously placed in Parglogenia, is synonymized with Xanthomelon durvillii (Hombron & Jacquinot, 1841).